Association between Periodontal Health and Stroke: Results from the 2013-2015 Korea National Health and Nutrition Examination Survey (KNHANES) - Min-Jeong Cho; Young-Seok Kim; Eun Young Park; Eun-Kyong Kim (Elsevier, 2021)
Background/purpose: As the population ages, the prevalence of stroke increases, and as such there has been increasing interest in the risk factors associated with stroke. Although an association between periodontitis and stroke has been suggested, there has been no study of this association among the Korean population. Therefore, we investigated the association between periodontal health and stroke among Korean adults. Materials and methods: A total of 9497 adults aged ≥40 years representing the Korean population were included in this cross-sectional study from the Korea National Health and Nutrition Examination Survey (KNHANES) VI (2013-2015). Periodontitis was diagnosed by dentists based on the Community Periodontal Index (CPI). Also, participants filled out a questionnaire regarding their experience of doctor-diagnosed stroke. Hypertension, diabetes, body mass index (BMI), and oral hygiene behavior covariates were adjusted in logistic regression analysis. Results: The mean age of the study population was 55.71 ± 0.17 years and 52.7% of them were female. Also, 248 people had a history of having a stroke. Results of the logistic regression analysis after adjusting for age and sex showed a significant relationship between oral health behavior, periodontal health, and stroke even after adjusting for age, sex, education, household income, national health insurance, employment status, alcohol, smoking, diabetes, hypertension, BMI, and oral health behaviors (odds ratio [OR], 1.71; 95% confidence interval [CI] = 1.03-2.85). Conclusion: Our findings suggest that periodontitis is associated with stroke in Korean adults.